"Colonization routes and demographic history of Chirostoma humboldtianum in the central Mexican plateau". Issue 4 (18th August 2020) - García‐Martínez, Rosa María; de los Angeles Barriga‐Sosa, Irene; López, Benjamín; Mejía, Omar
Abstract: In the present study we evaluate the population structure and potential colonization routes of the silverside Chirostoma humboldtianum through approximate Bayesian computations . Six microsatellite loci were amplified in a total of 288 individuals from six different locations covering the complete geographic distribution of the species. Additionally, two mitochondrial DNA markers, a D loop control region and cytochrome b were amplified in a subset of 107 individuals. The results found with microsatellites allow recovering well‐structured populations that have experienced a drastic reduction in the effective population size. On the other hand, mtDNA sequences showed a moderate phylogeographic structure with shared haplotypes between geographic localities and signalsof a slight increase in the effective population size. Finally, the approximate Bayesian computation analysis performed with both datasets suggested a west‐to‐east colonization route for the species in Central Mexico.